Circular Economy Design towards Zero Waste: Laying the foundation for constructive stakeholder engagement on improving construction, renovation, and demolition (CRD) waste management. Issue 1 (1st December 2022) - Keena, Naomi; Rondinel-Oviedo, Daniel R.; Demaël, Hermine
Abstract: The city of Montréal is one of many cities worldwide who strive to cut the amount of waste they generate and advance towards zero waste in an effort to meet the Paris Agreement goals. Construction, renovation, and demolition (CRD) waste is a major contributor to urban waste streams but also an area where waste diversion and innovative waste management approaches could deliver significant reductions in waste. One such promising approach is that of circular economy which envisions a future where CRD waste is designed-out of the built environment by keeping construction materials in use. This paper presents a series of methods used to collect and organize data towards advancing circular thinking within CRD material management decision-making in Montréal and mobilizing engagement with the relevant data. Methods includes a detailed literature review, semi-structured interviews with stakeholders from across the building sector value chain followed by a thematic analysis. Collected data is mapped to the internationally recognized United Nations Sustainable Development Goals (SDGs) framework in an aim to provide globally significant methodologies which cities worldwide can use to showcase contributions to the UN SDGs. Advancing towards zero CRD waste in Montréal will require the input of multiple stakeholders. The work presented in this paper is part of a larger research effort which works to deliver an initial but vital first step in the collection, integration, and dissemination of data towards a circular, more sustainable, built environment.